2012
DOI: 10.1063/1.4769744
|View full text |Cite
|
Sign up to set email alerts
|

Wood anomaly transmission enhancement in fishnet-based metamaterials at terahertz frequencies

Abstract: Rayleigh and Wood anomalies in the diffraction of acoustic waves from the periodically corrugated surface of an elastic medium Low Temperature Physics 42, 354 (2016);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These insights are crucial for the correct design of efficient complementary metasurfaces for research [11][12][13] and applications for example as narrow band filters [24] or sensing. [49]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These insights are crucial for the correct design of efficient complementary metasurfaces for research [11][12][13] and applications for example as narrow band filters [24] or sensing. [49]…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Subwavelength elements of various materials [9,10] enable to funnel, guide, and concentrate electric or magnetic fields beyond diffraction limits in subwavelength volumes, e.g., for nonlinear optics [11] or light-matter subwavelength spacing condition. As we will show, these conditions lead to the excitation of surface plasmon polaritons (SPP) modes [43][44][45][46] reminiscent of Wood's anomalies [47][48][49] which couple to the localized LC-modes of the meta-atom cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz (THz) on-chip planar metamaterials have emerged as an important active and passive device with different functionalities, such as sensing [1][2][3], extraordinary transmission [4][5][6][7], and asymmetric transmission [8]. In order to enhance light-matter interactions at a very fundamental level, many of the applications require metamaterials that support sharp resonances with high quality factor (Q) associated with high field enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials (MMs) are manmade engineered material to exhibit fascinating optical properties not occurring in nature, such as negative refractive index [1][2][3][4], perfect lens [5,6], electromagnetic cloaking [7,8],extraordinary transmission [9] and asymmetric transmission [10].Recently, MMs have become a flourishing research in the terahertz domain demonstrating application potential in sensing [11]. In order to make MMs perform efficiently on biological sensing, a resonance with a high quality factor (defined by the resonant frequency over width of the resonance) is desired [12,13].However, conventional planar MMs normally have a modest Q factor due to the rather small volume confinement of electromagnetic fields and strong coupling to vacuum [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the works demonstrate FRs in planar MMs based on a single metallic layer. It has been suggested that multiple layers of perforated metal-dielectric-metal(MDM) stacks (for 100 and 200 layers) along the propagation direction established a promising approach for a three dimensional (3D) optical MM [32][33][34].Such a 3D MM can possess a thickness much larger than the free space wavelength in the near infrared(NIR) region and excite a strong magnetoinductive coupling between neighboring functional layers under a normally incident light [33].The tight coupling between adjacent LC resonators through mutual inductance results in a low loss [35].Therefore, achievement of 3D multilayer MMs is an inevitable requirement for nearly all possible applications, like cloaking and invisible materials [33][34][35][36] [11]. It is realistic and well known that broken symmetry of the planar MM structures can result in a high order mode thus enhancing the FRs [42].However, to the best of our knowledge, limited research work looks at the influence of the symmetry breaking in MDM multilayer MMs on the FRs, specifically in the NIR regime considering the potential of the NIR spectrum for sensing.…”
Section: Introductionmentioning
confidence: 99%